EDTAKI: a Nephrology and Public Policy Committee platform call for more European involvement in acute kidney injury. Issue 4 (2nd February 2021) - Vanholder, Raymond; Rondeau, Eric; Anders, Hans-Joachim; Carlson, Nicholas; Fliser, Danilo; Kanbay, Mehmet; Lopes, José António; Murray, Patrick T; Ortiz, Alberto; Sanz, Ana B; Selby, Nicholas M; Wiecek, Andrzej; et al.
Abstract: Background: Acute kidney injury (AKI) is an often neglected but crucial element of clinical nephrology. The aim of the Nephrology and Public Policy Committee (NPPC) of the European Renal Association–European Dialysis and Transplant Association is to promote several key aspects of European nephrology. One of the targets proposed by the NPPC was to advance European nephrology involvement in AKI. Methods: We undertook a literature analysis to define the current position of European nephrology in the field of AKI compared with other regions and to determine how different European countries compare with each other. Results: It appeared that vis-à-vis countries with a comparable socio-economic status (the USA, Australia, New Zealand and Canada), the European contribution was almost 50% less. Within Europe, Central and Eastern Europe and countries with a lower gross domestic product showed lower scientific output. Nephrologists contributed to less than half of the output. There was no trend of a change over the last decade. Conclusions: There is room to improve the contribution of European nephrology in the field of AKI. We propose a model on how to promote clinical collaboration on AKI across Europe and the creation of a pan-European nephrology network of interested units to improve clinical outcomes, increase nephrologist involvement and awareness outside nephrology and stimulate research on AKI in Europe. Accordingly, we also propose a list of research priorities and stress the need for more European funding of AKI research.